(untitled) (Philological Studies, 2019)
The article aims to address the issue of a growing tendency of Slovene native speakers towards borrowing English personal names when naming their new-borns. Data supplied by the Statistical Office of the Republic of Slovenia (SURS) confirm that foreign (and, with that, English) names have increased in the past decades. Statistical lists compiled for the 1961-1970 decade and the 2001-2015 period illustrate how in the case of personal names, ‘exoticisms’ (e.g. Alex, Liam, Nick, Ruby, and Zoe, listed among the most popular 200 first names in the 2001-2015 period) compete with name forms that have been adapted and nativised long ago (e.g. Robert), or are currently being introduced for the first time into Slovene. The influx of name borrowings is discussed from the point of view of pragmatic borrowing as advocated by G. Andersen (2014). A historical overview of the borrowing of English personal names into Slovene is given, and the role of English as the model discussed. Such pragmatically borrowed items carry significant sociolinguistic signals about the borrowers’ attitudes, and these are analysed, based on questionnaires completed by parents of children aged 2-6. The cultural significance of English influence is thus sought to be evaluated.